(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The religious and worldly views reflected in the novel "Equilibrium" by the famous Uzbek writer Ulugbek Hamdam are the subject of this article, and the images of religion and faith in the work are analyzed in relation to modern society.